2013
DOI: 10.1007/s10815-013-0140-9
|View full text |Cite
|
Sign up to set email alerts
|

Variants in DPF3 and DSCAML1 are associated with sperm morphology

Abstract: Purpose Abnormalities in semen parameters are often associated with reduced fertility in males, and may, in part, be attributed to genetic variation. Aim of this study is to determine if genetic variants that were previously shown to be predictors of family size and birth rate in healthy men are also associated with sperm morphology in men recruited from an infertility laboratory. Methods Genetic associations with sperm morphology phenotypes in 126 ethnically diverse men from Chicago at 41 independent loci, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…Semen analysis is the way to determine the potential fertility of a male. Traditionally, sperm concentration, motility and morphology are the basic characteristics included in a spermiogram for all mammalian species, among which sperm morphology is most relevant with the genetics of the male (Landry et al, 2003;Sun, Ko & Martin, 2006;Kosova et al, 2014;Ray et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Semen analysis is the way to determine the potential fertility of a male. Traditionally, sperm concentration, motility and morphology are the basic characteristics included in a spermiogram for all mammalian species, among which sperm morphology is most relevant with the genetics of the male (Landry et al, 2003;Sun, Ko & Martin, 2006;Kosova et al, 2014;Ray et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We also found that semen progressive motility (Grade a + b) was greatly reduced in CT heterozygotes ( P = 0.0003) and the concentration of semen in CT heterozygotes was also low ( P = 0.0319). DPF3 encodes a member of the D4 protein family of zinc finger proteins which is implicated as an epigenetic factor specifically binding acetylated and methylated lysine residues of histone 3 and histone 4 to provide easy access of transcription factors to DNA 1516…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that rs10129954 in an intron of the DPF3 gene was correlated with both poor motility and sperm count. Kosova et al 616. found rs10129954 associated with total motile count, beat frequency and linearity, and sperm morphology in men from Chicago.…”
Section: Discussionmentioning
confidence: 99%
“…The DSCAML1 gene, 6 Mb away from the significant SNP BTA‐123344‐no‐rs , was found to increase the occurrence of sperm head defects and to be associated with poor sperm morphology, sperm production and the male reproductive process (Kosova et al . ).…”
Section: Descriptive Statistics Of the Deregressed And Original Estimmentioning
confidence: 97%